The Early Childhood Learning Models Based on the Local Wisdom in Madrasah Qudsiyyah Kudus - Khasan Ubaidillah (International Islamic Schools Alliance, 2016)
This research is motivated by the declining phenomenon of the Kudus society’s understanding on local wisdom which becomes the character and philosophy of their life, that is Gusjigang which contains the characters of Bagus Lakune (good behavior), Iso Ngaji (good at reciting Qur’an and ‘Kitab Kuning’), and Iso Dagang (good at trading/merchant). Thus it is necessary a means that can be a solution to reaffirm the understanding values of Kudus society. For the author, the agenda of strengthening the local wisdom values will be more effectives when carried out through education and integrative learning that unify text and context of life. Due to this means will facilitate the achievement of local wisdom understanding through the material and the interaction that occurs between individuals in learning. In order to get more influential impact, then it presumably should begin at the early age, as implemented in Madrasah Qudsiyyah Kudus. Since in the golden age, the absorbing power of the child's brain on the received knowledge is much greater than when they had grown and mature, therefore by implementing Gusjigang values (local wisdom of Kudus) in the early age of children will leave a positive behavior as the foundation for their future. This research aims to take a picture in detail about the early childhood learning in Madrasah Qudsiyyah comprehensively, thus the expectation is to find an ideal learning model related to the local wisdom-based learning for the early age children.